Mapping the digitalization in SMEs of Middle East region: trends and insights from bibliometric analysis - Abhishek Tripathi (Future Business Journal)
Abstract Digitalization is very important for SMEs in the Middle East in order to remain competitive and sustainable in this region. Therefore, the study aims to examine the digitalization in SMEs of the Middle East region using bibliometric analysis by considering publication trends, top authors, journals, articles, countries, and major keywords. The researchers used the Scopus database for data extraction and VOSViewer for the bibliometric analysis of this study. The findings revealed that countries from the Middle East realized the importance of digitalization after 2015, and the research trend rose after 2019 with highest publication count till 2023–24 in this domain. Furthermore, the bibliometric analysis revealed Saudi Arabia being the most influential country due to the highest numbers of publications in this domain. Rana. N.P., as the most influential author from Qatar, revealed Sustainability (Switzerland) is the most influential journal, while “Digitalization and economic growth: A comparative analysis of sub-Saharan Africa and OECD economies” is the highly cited article, and Digital Transformation is the highly co-occurred keyword in relation to digitalization of SMEs in the Middle East. Based on these findings, the study proposed managerial implications for policymakers in SMEs of the target region, and avenues for future researchers in this domain.